PENGARUH DAYA TARIK INTERPERSONAL TERHADAP HUBUNGAN INTERPERSONAL PADA REMAJA DI KOTA - Nazhifi Aufar Moza Alzura; Risna Febriani (PSIKOWIPA (Psikologi Wijaya Putra), 2023)
Interpersonal relationship is a relationship consisting of two or more people who are dependent on one another and use a consistent pattern of interaction. This interpersonal relationship includes familiarity, control, appropriate response, and harmony in the emotional atmosphere when communication takes place. This study aims to determine the effect of interpersonal attractiveness on interpersonal relationships in adolescents in the city of Banjarmasin. This research method uses a quantitative approach with Pearson's Product Moment analysis. Sampling in this study used a purposive sampling technique. The subjects in this study were teenagers in the city of Banjarmasin as many as 200 subjects. Measuring tools used in this study is the interpersonal attractiveness scale and interpersonal relationship scale. The results of this study are that there is a significant influence between interpersonal attractiveness and interpersonal relationships in adolescents in the city of Banjarmasin with R Square obtained at 0.278 and a significance level of 0.000.